Dynamic Approaches to Teacher Training: Enhancing Communicative Competence in English Education - Rahmonova Charos Farrukh qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
In a fast-paced, globalized educational landscape, the necessity for teachers proficient in communicative competence is more critical than ever. This thesis explores innovative and dynamic approaches to teacher training that focus on enhancing these competencies among future English educators. By integrating contemporary methodologies such as gamification, flipped classrooms, and cooperative learning, this work aims to provide effective strategies for developing communicative skills that meet the diverse needs of learners. The research highlights the importance of adapting teacher training programs to foster interactive and engaging learning environments that prepare educators for real-world challenges.